EMOTIONAL INTELLIGENCE OF SENIOR NURSE MANAGERS IN A TERTIARY HOSPITAL: AN ASSESSMENT - Cecilia O. Martinez; Kathleen G. de Leon; Ornest S. Santos; Adelson V. Aviguetero; Kenneth Lita; Ferdinand A. Lazaro (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This descriptive correlational study assessed the emotional intelligence of senior nurse managers in a tertiary hospital utilizing the “Schutte Self-report Emotional Test (SSEIT)” by Schutte et al. (2009). Results showed that most senior nurse managers belonged to the 36-40-year-old group; female; married; have served in their current position for more than 5 years but less than 10 years; BSN holders; and Roman Catholic. They have a moderate level of emotional intelligence in all the dimensions: Perception of Emotion, Managing Own Emotions, Managing Other Emotions, and Utilization of Emotion. There was a significant relationship between the senior nurse managers’ profile sex and their level of emotional intelligence in all the dimensions except managing their own emotions; the senior nurse managers’ profile years served in the current position, and their level of emotional intelligence in the dimension - utilization of emotion; and lastly, there were no significant relationships as to their age, sex, marital status, educational qualification, or religion and their level of emotional intelligence in all the dimensions. It was recommended that senior nurse managers must be: willing to explore more and understand emotions – theirs and others; continue practicing mindfulness and be attentive to their thoughts, feelings, and reactions in various situations in the workplace; utilize their inner strength and resilience to steer difficult situations in the hospital with grace and composure like stepping outside their comfort zone even when it feels uncomfortable so they can seek new experiences and perspectives and embrace opportunities for emotional growth and self-discovery; lastly, they must continue practicing active listening skills and being connected with others like their co-workers or their patients on a deeper emotional level.